PEMANFAATAN MULTIMEDIA INTERAKTIF KONSEP USAHA DALAM PELAJARAN FISIKA BERBASIS TEKNOLOGI INFORMASI - Erlansyah, Deni (Universitas Bina Darma, 2015)
Abstract: This paper describes an interesting scientific information processing application using SwishMax. Said to be interesting because in interactive media, there are features of navigation, so that users get easily get the information they need. Method used is to study literature. Some literature is analyzed to provide an overview of the advantages of information processing in interactive media. Outlined also making navigation features required by users of information. One platform that can be used to create an interactive multimedia-based learning media is Swish-Max. Swish-Max is a combination of learning concept with audiovisual technology capable of producing the new features that can be used in learning. Features Features that exist in the Swish-Max is able to design animations more attractive, not monotonous and memudahkanpenyampaian material. The aim is to help facilitate teachers and students in providing and understanding the material effort in physics. Keywords: Information Processing, SwishMax Application, Interactive Multimedia, Navigation.